Biomedical applications of artificial exosomes for intranasal drug delivery - Zhao, Jinming; Yang, Jingxing; Jiao, Jian; Wang, Xiangdong; Zhao, Yan; Zhang, Luo (Frontiers in Bioengineering and Biotechnology, 2023)
Intranasal administration offers a feasible, non-invasive method of delivering therapeutic drugs to the brain, allowing therapeutic pharmaceuticals to be administered directly to the central nervous system by bypassing the blood-brain barrier. Furthermore, exosomes are naturally occurring cell-derived nanovesicles that can serve as carriers for a variety of chemical compounds. Many studies have focused on artificial exosomes as innovative medication delivery methods. As a result, trans-nasal delivery of artificial exosomes might be employed to treat brain illnesses in a novel method. This review will outline the drug delivery mechanism of artificial extracellular vesicles, emphasize its advantages as a nasal drug carrier, particularly its application as a novel nanocarriers in brain diseases, and focus on its prospective application in chronic inflammatory nose disorders. Finally, artificial exosomes may become a unique drug delivery mode for clinical therapeutic usage.